HTML-Based Website Learning Training (Hypertext Markup Languange) - Rahmatika Rahmatika; Ulfa Pauziah; Hardian Mursito (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
In today's era of globalization, websites are very familiar, where many people easily use the web or website. Some can make their own and some ask for it to be made or rather buy. Just use it and then we just need to use it. Our partners are neighborhood associations 05 and 06 which are located in Perumnas Depok Timur, which have young women and men who are curious about website development, and some young women and men want to continue their studies at a higher level by majoring in information and communication. In making a website, they need several stages that they have to apply because our partners are teenagers who are unfamiliar with website creation, for that we here want to make a basic training in website creation which will later be useful for them in terms of application in their environment and society. Where in this training introduced HTML (hypertext markup language). It is hoped that by studying HTML, teenagers can understand how to create a website with HTML.